Finance, Financial Sector Policies, and Long-Run Growth - Demirgüç-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2012)
The first part of this paper reviews the literature on the relation between finance and growth. The second part of the paper reviews the literature on the historical and policy determinants of financial development. Governments play a central role in shaping the operation of financial systems and the degree to which large segments of the financial system have access to financial services. The paper discusses the relationship between financial sector policies and economic development.